If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -5 = 34 + -6x Reorder the terms: -5 + 7x = 34 + -6x Solving -5 + 7x = 34 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. -5 + 7x + 6x = 34 + -6x + 6x Combine like terms: 7x + 6x = 13x -5 + 13x = 34 + -6x + 6x Combine like terms: -6x + 6x = 0 -5 + 13x = 34 + 0 -5 + 13x = 34 Add '5' to each side of the equation. -5 + 5 + 13x = 34 + 5 Combine like terms: -5 + 5 = 0 0 + 13x = 34 + 5 13x = 34 + 5 Combine like terms: 34 + 5 = 39 13x = 39 Divide each side by '13'. x = 3 Simplifying x = 3
| -(r-4)-5(r-7)=4r+6+6+1 | | 4y+37=9 | | 3(2+u)-u=4+2(u+1) | | 4(x-2)=1 | | 2x-3(1)=5 | | 149=5/9(f-32) | | 14p+-3p=-11 | | 18(18-3x)=2(6-14x) | | 6+4(x+5)-x= | | 3n-5n+4+4n=36 | | 6b^2-12b-210=0 | | 120x=180(5-x) | | 2y+2=2y+1 | | x+4*2+2x= | | 3x(x+20)=60 | | 5(x+3)-(x-7)= | | -4(-14-19a)=7(11a+20)-a | | (6+w)(3w+7)=0 | | 3x+8y=9(y+2y+7) | | 13c+51c=-26 | | -11=x+8x+7 | | 5y+5=y(8-2y) | | 13(x-3)-22x=-18 | | v=3.14(3.14)(h) | | x+18+2x=-14-2x-18 | | X+(2x+0.10)=2.5 | | 2x+n=3 | | 95+52a=303 | | y=x^2-11x+20 | | 0.5x+0.4=0.08x-0.5 | | 5b+20=1.75 | | 6x-4=3x-28 |